2015
DOI: 10.1093/glycob/cwv019
|View full text |Cite
|
Sign up to set email alerts
|

Sialidases as regulators of bioengineered cellular surfaces

Abstract: Human sialidases (NEUs) catalyze the removal of N-acetyl neuraminic acids from the glycome of the cell and regulate a diverse repertoire of nominal cellular functions, such as cell signaling and adhesion. A greater understanding of their substrate permissivity is of interest in order to discern their physiological functions in disease states and in the design of specific and effective small molecule inhibitors. Towards this, we have synthesized soluble fluorogenic reporters of mammalian sialidase activity bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that substitutions on the N-acyl side chain of sialic acid can affect sialidase activity in vitro, although these effects are isoenzyme specific. In addition, while sialic acid analogs bearing larger N-acyl groups are generally poor substrates for purified sialidases, some secreted sialidases appear to be more tolerant of these substitutions in metabolically labeled cells . Thus, addition of diazirine to the N-acyl side chain of sialic acid could result in altered activity of sialidases, such that certain sialidases may be able to selectively cleave Neu5Ac, but not SiaDAz­(2me) or SiaDAz­(4me), from glycoconjugates.…”
mentioning
confidence: 99%
“…Previous studies have shown that substitutions on the N-acyl side chain of sialic acid can affect sialidase activity in vitro, although these effects are isoenzyme specific. In addition, while sialic acid analogs bearing larger N-acyl groups are generally poor substrates for purified sialidases, some secreted sialidases appear to be more tolerant of these substitutions in metabolically labeled cells . Thus, addition of diazirine to the N-acyl side chain of sialic acid could result in altered activity of sialidases, such that certain sialidases may be able to selectively cleave Neu5Ac, but not SiaDAz­(2me) or SiaDAz­(4me), from glycoconjugates.…”
mentioning
confidence: 99%
“…3 The sialidases were selected on the basis of their species and colonization site diversity, as well as their known broad substrate specificity. 6 To screen bacterial sialidases activity against our unnatural sialosides, we developed an in vitro enzymatic 1 H NMR coupled assay which, unlike previous methods, 7,26 is fully compatible with 5-and 9-modified sialic acids, various sialyl linkage specificities, as well as the composition of the underlying glycans. Accordingly, sialosides 1−10 were individually incubated with either C. perfringens, S. pneumoniae, V. cholerae, or S. typhimurium sialidase at 37 °C in acetate buffer made from deuterated water (50 mM, pH 5.5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Glycocalyx shedding is regulated by glycocalyx shedding enzymes. Hyaluronidase (HYAL) (Dogne et al, 2016), heparanases (HPSE) (Arfian et al, 2019), matrixmetalloproteinases (MMP) (Ramnath et al, 2014), neuraminidase (NEU) (Mensah et al, 2019; Zamora et al, 2015) and hyaluronic acid synthetase (HAS) (Zhang et al, 2018) are directly involved in glycocalyx degradation. These enzymes can trigger glycocalyx shedding.…”
Section: Introductionmentioning
confidence: 99%